2006
DOI: 10.1021/bi051594r
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Chromogranin B in Inositol 1,4,5-Trisphosphate-Mediated Nuclear Ca2+ Mobilization

Abstract: Recently, secretory granule Ca(2+) storage protein chromogranin B (CGB) was shown to be present in the nucleoplasm proper in a complex structure that consists of the inositol 1,4,5-trisphosphate receptor (IP(3)R)/Ca(2+) channels and the phospholipids. Further, the amounts of IP(3)Rs present in the nucleus of bovine chromaffin cells were shown to be comparable to that of the endoplasmic reticulum. Therefore, we investigated here the potential contribution of nuclear CGB on the IP(3)-dependent Ca(2+) mobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Interference of the interaction between chromogranins and InsP 3 R with an expressed chromogranin peptide targeted to the ER lumen in neuronally differentiated PC12 cells, inhibited Ca 2ϩ release response to the muscarinic agonist carbachol (87). CGB is also found in the nucleus in a complex with phospholipids and the InsP 3 R, and it has been suggested that the interaction could modulate InsP 3 -dependent Ca 2ϩ signaling within the nucleoplasm (194).…”
Section: Chromograninsmentioning
confidence: 99%
“…Interference of the interaction between chromogranins and InsP 3 R with an expressed chromogranin peptide targeted to the ER lumen in neuronally differentiated PC12 cells, inhibited Ca 2ϩ release response to the muscarinic agonist carbachol (87). CGB is also found in the nucleus in a complex with phospholipids and the InsP 3 R, and it has been suggested that the interaction could modulate InsP 3 -dependent Ca 2ϩ signaling within the nucleoplasm (194).…”
Section: Chromograninsmentioning
confidence: 99%
“…1A) were constructed as described under "Experimental Procedures." Full-length CGB and its fragments were expressed in NIH3T3 cells, a mouse fibroblast cell line without endogenous CGB (10). Expression and localization were determined via Western blotting (Fig.…”
Section: Expression Of Cgb and Fragments In Nih3t3 Cellsmentioning
confidence: 99%
“…In view of the presence of the majority of cellular calcium, IP 3 R/Ca 2+ channels, and chromogranins in secretory granules, which is necessary for an organelle to function as the major IP 3 ‐sensitive intracellular Ca 2+ store, it would be natural for secretory granules to play the most significant role in the IP 3 ‐dependent intracellular Ca 2+ control mechanism. Whether secretory granules play the major role in the cytoplasmic IP 3 ‐dependent Ca 2+ control mechanism could be discerned by comparing the magnitudes of the IP 3 ‐mediated Ca 2+ releases between the cells that contain different numbers of secretory granules (27, 83).…”
Section: Secretory Granules Are Responsible For the Majority Of Ip3‐imentioning
confidence: 99%
“…Given that only the number of secretory granules formed is reduced in the cytoplasm, these results indicate that secretory granules are responsible for the majority of IP 3 ‐mediated cellular Ca 2+ release in the cytoplasm of neuroendocrine PC12 cells (27). On the other hand, induction of secretory granule formation by expressing chromogranins in nonneuroendocrine NIH3T3 cells that normally do not contain any secretory granules markedly increased the magnitude of IP 3 ‐induced Ca 2+ release of these cells (27, 83). When secretory granule formation was induced by expressing CGA in NIH3T3 cells, the magnitude of IP 3 ‐induced Ca 2+ release in the cytoplasm of NIH3T3 cells increased ~2.7‐fold over the control (Fig.…”
Section: Secretory Granules Are Responsible For the Majority Of Ip3‐imentioning
confidence: 99%